PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN PROPORSI KOMISARIS INDEPENDEN TERHADAP PENGUNGKAPAN EMISI KARBON PADA PERUSAHAAN PERTAMBANGAN - Agung Setiawan; Pramandyah Fitah Kusuma (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2023)
This study aims to examine and analyze the effect of profitability, company size, and the proportion of independent commissioners on carbon emission disclosure in mining companies listed on the Indonesia Stock Exchange with the sampling technique used in this study is purposive sampling and obtained 36 company data as samples. Data analysis was performed using statistics using SPSS Version 26 tools. Based on the results of data analysis using the t test, it is known that partially Profitability, Company Size and Proportion of Independent Commissioners do not have a significant effect on carbon emission disclosure. And based on the results of test f it is known that simultaneously Profitability, Company Size and Proportion of Independent Commissioners do not have a significant effect on carbon emission disclosure.